Kelompok Ibu Cerdas TPA Cipayung: Produksi Sabun Minyak Jelantah sebagai Upaya Zero Waste - Terry Y. R. Pristya; Azizah M Fitri; Fajaria Nurcandra (Jurnal Pengabdian Pada Masyarakat, 2020)
CIPAYUNG LANDFILL SMART GROUP: PRODUCTION OF WASTE COOCKING OIL SOAP FOR ZERO WASTE. Cipayung landfill was overload by garbage. Various environmental problems due to garbage are complained of by people who lived around the landfill, such as pollutions of water, air, and land. The zero waste was hope to be able to reduce problems there and not to add the new problems about the environmental. The study conducted on housewife in September 19th 2019 Cipayung Landfill Depok, West Java. We conducted activites as follows: counseling and workshop. The result showed that: there was significant knowledge between pre and post counseling with t-test (p value = 0,001). This study has also provided workshop to make waste cooking oil soap. This study increased participant’s knowledge regarding waste cooking oil, pollutions, and zero waste. Furthermore this studywas increased the productivity of housewive to reuse waste coocking oil in their home.